Impact of cardiac resynchronisation therapy on cardiologists' exposure to radiation during implantation of pacemakers and implantable cardioverter-defibrillators. (15th April 2019) - Daval, Charline; Faroux, Laurent; Lesaffre, François; Blanpain, Thierry; Chabert, Jean-Pierre; Martin, Angeline; Guinot, Mathias; Luconi, Nicolas; Espinosa, Madeline; Nazeyrollas, Pierre; Tourneux, Christophe; Metz, Damien
Abstract: Cardiologists are among the health professionals that are most exposed to ionizing radiation, but there is no recent study quantifying overexposure of physicians during cardiac resynchronisation therapy (CRT) procedures compared to 'classical' implantation of pacemakers (PMs) or implantable cardioverter-defibrillators (ICDs). We aimed to measure and compare operator exposure to radiation during implantation of PM and ICD with or without CRT. The study population comprised all PMs and ICDs implanted in a large referral centre over a six months period. The endpoint was operator radiation exposure, assessed using a personal electronic dosimeter located on operator's chest. In total, 169 PM/ICD implantations were analysed, 19 of which included CRT. Compared with 'classical' implantation, cardiologist radiation exposure was 9-fold greater during CRT procedures (p < 0.001). Physician exposure was related to dose-area product (R 2  = 0.21 during 'classical' implantations and R 2  = 0.57 during CRT procedures). Our study shows that cardiologists' exposure to radiation during CRT implantation was 9-fold greater than during procedures without CRT.